2002
DOI: 10.1096/fj.01-0690hyp
|View full text |Cite
|
Sign up to set email alerts
|

Regional manifestations and control of the immune system

Abstract: Although immune responses are generally considered to be systemic, local events such as interaction of complement products with blood vessels and with inflammatory cells play a pivotal role in determining the nature and manifestations of immune responses. This paper will discuss how blood vessel physiology and immunity influence one another to reach homeostasis upon exposure to an infectious agent. We review new insights into the mechanisms by which the microenvironment of tissues protects against microbial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 76 publications
0
97
0
7
Order By: Relevance
“…These changes include diminished availability of oxygen (hypoxia) [8][9][10] with subsequent lactate accumulation and resultant metabolic acidosis. Such shifts in tissue metabolism result, at least in part, from profound recruitment of inflammatory cells, in particular myeloid cells such as neutrophils (polymorphonuclear cells) and monocytes.…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 99%
“…These changes include diminished availability of oxygen (hypoxia) [8][9][10] with subsequent lactate accumulation and resultant metabolic acidosis. Such shifts in tissue metabolism result, at least in part, from profound recruitment of inflammatory cells, in particular myeloid cells such as neutrophils (polymorphonuclear cells) and monocytes.…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 99%
“…22 HS displays a multifactoral affect on the immune response. 23 In the early events, HS is involved in the complement cascade and the containment and walling off of infection through interaction with complement and platelets. In the intermediate stage, the role of HS in inflammation involves the regulation of the formation of chemotactic complement proteins triggering neutrophils to respond to chemokines and release proteases and oxidants and endothelial expression of P-selectin promoting neutrophil adhesion.…”
Section: Glycosaminoglycans In Cellular Communication Linhardt and Toidamentioning
confidence: 99%
“…Many studies have shown that inflammatory lesions are characterized by hypoxia (10)(11)(12)(13). Experimental studies further indicated that hypoxia directly activates the transcription of NF-κB and the expression of iNOS (14).…”
Section: Introductionmentioning
confidence: 99%